2018
DOI: 10.4269/ajtmh.17-0624
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-Cell Dynamics in Cutaneous and Mucocutaneous Leishmaniasis due to Leishmania braziliensis

Abstract: To evaluate the dynamics of regulatory T cells (Tregs) during tegumentary leishmaniasis, we assessed peripheral blood and biopsies from 54 patients. Patients with cutaneous leishmaniasis (CL) had a decreased proportion of Tregs in the peripheral blood, but the proportion was higher in the biopsies of lesions. During treatment of CL, circulating Tregs increased reaching normal proportions, whereas antigen-specific interferon-γ responses diminished. By contrast, circulating Tregs from mucosal leishmaniasis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Also, other research showed that Tregs were significantly higher in biopsies than in peripheral blood, corroborating our hypothesis 22 . The migration and homing of Tregs to the infection site are thought to be the result of the expression of several chemokines 21 . CCR5 plays a crucial role in the homing of Tregs at infection sites 19 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Also, other research showed that Tregs were significantly higher in biopsies than in peripheral blood, corroborating our hypothesis 22 . The migration and homing of Tregs to the infection site are thought to be the result of the expression of several chemokines 21 . CCR5 plays a crucial role in the homing of Tregs at infection sites 19 .…”
Section: Discussionsupporting
confidence: 87%
“…It is important to consider that Tregs are potentially migrating to the lesion site rather than circulating in the blood. 21 Moreover, Treg migration and homing to the infection site is driven by chemokines (CCs) and their detection through receptors (CCRs) is a way to evaluate it. 21 Also, other research showed that Tregs were significantly higher in biopsies than in peripheral blood, corroborating our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations